การทำให้บริสุทธิ์และลักษณะสมบัติของแอลฟา-แอล-อะราบิโนฟิวราโนสิเดสจาก Streptomyces sp. PC22 - ปิ่นปัญญา เรียงรุ่งโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Alfa-l-Arabinofuranosidase, one of xylan-debranching enzymes, was purified from the culture filtrate of streptomyces sp. PC22 grown in liquid medium containing oat spelt xylan as a carbon source. The enzyme was purified to approximately 111 folds with a recovery yield of 13.12% by fractionation with 40-90% saturation of ammonium sulfate followed by consecutive column chromatography on Macro-prep DEAE, butyl hydrophobic interaction and hydroxyapatite, respectively. The molecular weight of the purified enzyme was 317 kDa as estimated by gel filtration and composed of four identical subunits of 79 kDa estimated by SDS-PAGE. The enzyme had temperature and pH optima of 65 ํC and 6.0, respectively. It was stable to temperature up to 45 ํC for 30min and to a broad range of pH from 5.5-9.0. The K[subscript m] and V[subscript max] values of the enzyme for p-nitrophenyl alfa-l-arabinofuranoside were 0.27 mM and 3,926.15 mol/min/mg protein respectively. It was competitively inhibited by L-arabinose with K[subscript i] value of 15.08 mM. The enzyme activity was completely inhibited by Hg[superscript2+] and also inhibited by N-bromosuccinimide and phenylmethylsulfonyl fluoride indicating tryptophan and serine residue involved in catalytic mechanism. The purified enzyme did not exhibit xylanase, acetyl esterase and B-xylosidase acitivities.